Novice principals in Chile mobilizing change for the first time: Challenges and opportunities associated with a school's readiness for change. (March 2018) - Galdames, Sergio; Montecinos, Carmen; Campos, Fabián; Ahumada, Luis; Leiva, María Verónica
In a context characterised by triple sources of accountability demands, principals in Chile are required to mobilise change to raise performance indicators. School improvement is a complex endeavour—a complexity that is intensified for newly appointed principals, particularly when placed in a high-poverty, ineffective school. This article explores changes introduced by newly appointed principals placed in elementary public schools that were struggling ( n = 4) and in schools that were sinking ( n = 5). Findings show that all participants converged on actions to promote changes in: staffing, redesigning the organisation, and managing instruction. The quality of the actions, however, differed by type of school, highlighting the importance of defining policies for strengthening school leadership that take into account differences among schools. Induction will provide needed support at the individual level, but it might be insufficient support if other measures at the district level fail to create conditions, such as staffing, so the arrival of a new principal is indeed an opportunity to reverse a downward trajectory of an ineffective, high-poverty school.